Hubungan Berdiri Lama Dengan Terjadinya Nyeri Punggung Bawah Pada Pegawai Rotte Bakery Di Kota Pekanbaru Tahun 2020 - Retno Putri; Dea Vilia Siswoyo; Nurshal Hasbi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Low back pain (LBP) is a non-specific condition of acute or chronic pain in or near the lumbosacral spines that can be caused by inflammatory, neoplastic, traumatic, or other disorders. Long standing can be caused discomfort for the worker’s body. A survey conducted by the Center for Disease Control and Prevention (CDC) in 2011, low back pain is found in the top 10 diseases in Indonesia. As for jobs that required on standing for long duration and correlation by increased risk for low back pain, one of which is in a cake company called Rotte Bakery in Pekanbaru. The production process at Rotte Bakery required a lot of human roles, especially in terms of physical aspects, allowing staffs to long standing while working which can cause ergonomic problems such as low back pain. The research conducted by observational analytic method, with a cross sectional study design. The sampling technique used accidental sampling which was statistically tested using the chi-square test. The research purposes to determine the correlation of the long standing with low back pain event on Rotte Bakery Pekanbaru city staffs 2020. The result showed that there was a relationship (p-value = 0,000) and a significant correlation (p-value < 0.05) long standing with lower back pain event on Rotte Bakery Pekanbaru city staffs. Rotte Bakery staffs advised to pay attention to standing time while working, adhere to the rules for using a complete PPE, and the company can provide education at the beginning before starting work.